VEB-1-like extended-spectrum beta-lactamases in Pseudomonas aeruginosa, Kuwait. - Poirel, L (Centers for Disease Control and Prevention, 2001)
Two clinical Pseudomonas aeruginosa isolates from patients in intensive care units in Kuwait were resistant to expanded-spectrum cephalosporins and showed a synergistic effect between ceftazidime and clavulanic acid. This is the first report of extended-spectrum enzymes from nosocomial isolates from the Middle East.